ANALISIS IMPLEMENTASI PATIENT SAFETY TERHADAP PENINGKATAN KUALITAS PELAYANAN DI RSUD BATARA SIANG KAB. PANGKAJENE DAN KEPULAUAN TAHUN 2022 - Nurul Fitriyana Nurdin; Dian Ekawaty; Mohammad Ardani Samad; Hj. Afriyana Amelia N (Jurnal Penelitian Kesehatan Pelamonia Indonesia, 2024)
Patient Safety or commonly referred to as patient safety is a very important indicator in the medical system, which is expected to provide a reference for patients to create maximum health services and reduce accidents for patients (Canadian Patient Safety Institute (CPSI)). The purpose of the study was to determine the analysis of the implementation of safety efficiency towards improving service quality. The type of research used is quantitative research using the Cross Sectional Study approach, the population in this study is nurses who are in inpatient installations at Batara Siang Hospital, Pangkajene and Islands Regency, the sample in this study amounted to 176 nurse respondents. The sampling technique used is random sampling. The data collection techniques in this study, namely primary data and secondary data, were then analyzed using multiple linear regression analysis with the help of the SPSS 22 application. The results of this study showed that the study on the patient identification variable obtained a sig value = 0.031<0.05. Variable Improve effective communication obtained sig value = 0.274>0.05. variables of drug safety improvement that need to be watched out for obtained sig value = 0.012<0.05. variables Of certainty of exact location, exact procedure, exact patient operation obtained sig value = 0.131>0.05. the variable of reduction in the risk of health care-related infections obtained sig value = 0.038<0.05. And the variable of reducing the risk of falling injury in patients obtained sig value = 0.261>0.05. The conclusions in this study are patient identification, increased drug safety that needs to be watched out for, and reducing the risk of infection related to health services, there is a significant influence on improving the quality of service, and it is recommended to nurses at Batara Siang Hospital, Pangkajene Regency and Islands to pay attention to the green sticker mark for LASA (Look Alike Sound Alike) drugs so that there are no mistakes in drug administration.